2022
DOI: 10.3389/fpsyt.2022.972158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular actions of sex hormones in the brain and their potential treatment use in anxiety disorders

Abstract: Anxiety disorders are one of the most prevalent mood disorders that can lead to impaired quality of life. Current treatment of anxiety disorders has various adverse effects, safety concerns, or restricted efficacy; therefore, novel therapeutic targets need to be studied. Sex steroid hormones (SSHs) play a crucial role in the formation of brain structures, including regions of the limbic system and prefrontal cortex during perinatal development. In the brain, SSHs have activational and organizational effects me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…The relationship between corticosterone, depression, and sex hormones is complicated and controversial. Estradiol signaling might involve in regulation of HPA axis through estrogen receptors (Kokras et al., 2020; Pillerová et al., 2022). Molecular studies revealed that estradiol regulates corticotropin‐releasing hormone mRNA expression (Lalmansingh & Uht, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between corticosterone, depression, and sex hormones is complicated and controversial. Estradiol signaling might involve in regulation of HPA axis through estrogen receptors (Kokras et al., 2020; Pillerová et al., 2022). Molecular studies revealed that estradiol regulates corticotropin‐releasing hormone mRNA expression (Lalmansingh & Uht, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, men have testosterone hormone with an anxiolytic effect by reducing stress responses and suppressing the Hypothalamic-Pituitary-Adrenal (HPA) axis activity. 27 This explains why gonadal hormones play a role in women's higher prevalence of anxiety levels. Fluctuations in estrogenic and progesterone during the menstrual cycle affect the reactivation of the HPA axis and feedback response to glucocorticoids and Gamma-aminobutyric acid (GABA), resulting in a less stable hormonal balance than in men, contributing to anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, the sex steroid hormone has activating and organizational effects mediated by intracellular or transmembrane G-protein-coupled receptors. (35) It is important to study the relationship between steroid hormones with aging and cognitive function. Previously it was mentioned that the aging process is associated with changes in hormone levels (18,19) ; as a result, these hormone levels reduce several body functions, including cognitive function.…”
Section: Sex Steroid Hormone and Cognitive Function In The Elderlymentioning
confidence: 99%